2014
DOI: 10.1016/j.fishres.2014.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Using posts to an online social network to assess fishing effort

Abstract: a b s t r a c tFisheries management has evolved from reservoir to watershed management, creating a need to simultaneously gather information within and across interacting reservoirs. However, costs to gather information on the fishing effort on multiple reservoirs using traditional creel methodology are often prohibitive. Angler posts about reservoirs online provide a unique medium to test hypotheses on the distribution of fishing pressure. We show that the activity on an online fishing social network is relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…App data are also likely to complement, and in some cases provide a viable alternative to, conventional lake and angler surveys. For example, our analyses show that app data predict survey-based estimates of angler effort in most regions of Alberta as well as creel-based estimates of angler visits to specific Alberta lakes (see also Martin et al 2014). The latter relationship was less strong, perhaps because creel data preceded app data by up to 19 years.…”
Section: Benefits and Broad Applicationsmentioning
confidence: 78%
See 1 more Smart Citation
“…App data are also likely to complement, and in some cases provide a viable alternative to, conventional lake and angler surveys. For example, our analyses show that app data predict survey-based estimates of angler effort in most regions of Alberta as well as creel-based estimates of angler visits to specific Alberta lakes (see also Martin et al 2014). The latter relationship was less strong, perhaps because creel data preceded app data by up to 19 years.…”
Section: Benefits and Broad Applicationsmentioning
confidence: 78%
“…In addition, where other tools require a project to be launched, along with the need to train and motivate volunteers, apps can collect data passively. For example, a recent study found that passive data from a similar medium (an online angler forum) predicted spatial and temporal patterns of fishing effort in Nebraska reservoirs (Martin et al 2014). Therefore, fishing apps represent an underutilized tool for efficiently collecting information on angler behavior and other data relevant to fisheries management and invasive species control.…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis found that effort data from a popular angler app in Alberta, Canada, were comparable to creel and mail survey data at regional and seasonal scales (Papenfuss et al 2015; see also Martin et al 2014). These conventional methods are relatively expensive and time-consuming, and often limited in space and time.…”
Section: Opportunitiesmentioning
confidence: 99%
“…Only 12 of the 17 reservoirs included Omaha in their 95% area of influence, most of which are on the northern portion of the region, closer to Omaha, or are larger, more well-known reservoirs. This suggests that anglers are willing to travel farther to fish reservoirs that are more well-known and are perhaps discussed more frequently through either word-of-mouth communication or online social media (Martin et al 2014). Furthermore, the area of influence did not increase as the number of observations (i.e., anglers interviewed) increased, contrary to what has been suggested (Seaman et al 1999), indicating that our sample sizes were larger than those typical of studies using kernel density estimation.…”
Section: Discussionmentioning
confidence: 71%